The global cancer divide: Relationships between national healthcare resources and cancer outcomes in high-income vs. middle- and low-income countries - Ali Batouli; Pooya Jahanshahi; Cary P. Gross; Danil V. Makarov; James B. Yu (Springer, 2019)
Background: Cancer continues to rise as a contributor to premature death in the developing world. Despite this, little is known about whether cancer outcomes are related to a country's income level, and what aspects of national healthcare systems are associated with improved cancer outcomes. Methods: The most recent estimates of cancer incidence and mortality were used to calculate mortality-to-incidence ratio (MIR) for the 85 countries with reliable data. Countries were categorized according to high-income (Gross Domestic Product (GDP) > $15,000) or middle/low-income (GDP < $15,000), and a multivariate linear regression model was used to determine the association between healthcare system indicators and cancer MIR. Indicators study included per capita GDP, overall total healthcare expenditure (THE), THE as a proportion of GDP, total external beam radiotherapy devices (TEBD) per capita, physician density, and the year 2000 WHO healthcare system rankings. Results: Cancer MIR in high-income countries (0.47) was significantly lower than that of middle/low-income countries (0.64), with a p < 0.001. In high-income countries, GDP, health expenditure and TEBD showed significant inverse correlations with overall cancer MIR. A $3040 increase in GDP (p = 0.004), a $379 increase in THE (p < 0.001), or an increase of 0.59 TEBD per 100,000 population (p = 0.027) were all associated with a 0.01 decrease in cancer MIR. In middle/low-income countries, only WHO scores correlated with decreased cancer MIR (p = 0.022); 12 specific cancer types also showed similar significant correlations (p < 0.05) as overall cancer MIR. Conclusions: The analysis of this study suggested that cancer MIR is greater in middle/low-income countries. Furthermore, the WHO healthcare score was associated with improved cancer outcomes in middle/low-income countries while absolute levels of financial resources and infrastructure played a more important role in high-income countries.